Hippocampus ghrelin receptor signaling promotes socially-mediated learned food preference - Hsu, Ted M. (Neuropharmacology, 2017)
Social cues are potent regulators of feeding behavior, yet the neurobiological mechanisms through which social cues influence food intake are poorly understood. Here we investigate the hypothesis that the appetite-promoting gut-derived hormone, ghrelin, signals in the hippocampus to promote learned social aspects of feeding behavior. We utilized a procedure known as ‘social transmission of food preference’ (STFP) in which rats (‘Observers’) experience a social interaction with another rat (‘Demonstrators’) that recently consumed flavored/scented chow. STFP learning in Observer rats is indicated by a significant preference for the Demonstrator paired flavor of chow vs. a novel unpaired flavor of chow in a subsequent consumption choice test. Our results show that relative to vehicle treatment, ghrelin targeted to the ventral CA1 subregion of the hippocampus (vHP) enhanced STFP learning in rats. Additionally, STFP was impaired following peripheral injections of L-cysteine that reduce circulating ghrelin levels, suggesting that vHP ghrelin-mediated effects on STFP require peripheral ghrelin release. Finally, the endogenous relevance of vHP ghrelin receptor (GHSR-1A) signaling in STFP is supported by our data showing that STFP learning was eliminated following targeted viral vector RNA interference-mediated knockdown of vHP GHSR-1A mRNA. Control experiments indicate that vHP ghrelin-mediated STFP effects are not secondary to altered social exploration and food intake, nor to altered food preference learning based on nonsocial olfactory cues. Overall these data reveal a novel neurobiological system that promotes conditioned, social aspects of feeding behavior.